Physiological Roles of Apoptotic Cell Clearance: Beyond Immune Functions - Minjoo Han; Gyoungah Ryu; Seong-Ah Shin; Jangeun An; Huiji Kim; Daeho Park; Dae-Hee Lee; Chang Sup Lee (Life, 2021)
The clearance of apoptotic cells is known to be a critical step in maintaining tissue and organism homeostasis. This process is rapidly/promptly mediated by recruited or resident phagocytes. Phagocytes that engulf apoptotic cells have been closely linked to the release of anti-inflammatory cytokines to eliminate inflammatory responses. Defective clearance of apoptotic cells can cause severe inflammation and autoimmune responses due to secondary necrosis of apoptotic cells. Recently accumulated evidence indicates that apoptotic cells and their clearance have important physiological roles in addition to immune-related functions. Herein, we review the current understanding of the mechanisms and fundamental roles of apoptotic cell clearance and the beneficial roles of apoptotic cells in physiological processes such as differentiation and development.